Application Of EOQ & ROP For Inventory Control At Umkm Jasa Barona - Caniago, Putri Ranggaini; Marliyah, Marliyah; Nurlaila, Nurlaila (UNIVERSITAS PAKUAN, 2017)
Grosir Jasa Barona is a wholesaler located in Tuasan, selling various daily necessities including staple goods. The location was chosen due to inventory management issues at the wholesaler, where stock is ordered once a month in quantities predetermined by the owner. Despite this, the inventory often results in overstock or stock shortages. This research aims to assist in establishing proper inventory management at the wholesaler by implementing the Economic Order Quantity (EOQ) and Reorder Point (ROP) methods. The EOQ method was selected to determine the optimal quantity of staple goods to order, while the ROP method helps identify the appropriate timing for reordering. The focus of this study is to improve inventory management at Grosir Jasa Barona. A qualitative approach was used, employing both primary and secondary data, with data collected through direct observation and interviews. The results showed that using EOQ and ROP methods can significantly improve inventory management at this Tuasan-based wholesaler. The implication of this research is that effective inventory management can lead to better cost control and increased profitability for the business.